Social entrepreneurship and organisational effectiveness: evidence from Malaysia - Zainol, Fakhrul Anwar; Wan Daud, Wan Norhayate; Abdullah, Zulhamri; Yaacob, Mohd Rafii (Inderscience, 2015)
Malaysia has made great strides in eradicating poverty. Based on the latest figures of the 9th Malaysian Plan Mid-term Review, the overall hard core poverty percentage is down to 0.7%, and only 3.6% of the Malaysian population is living below the overall poverty line. The government has taken efforts successfully through various developmental projects to alleviate poverty in rural area. Today, urban poverty in Malaysia has increasingly visible phenomenon due to rural-urban migration and the natural population growth in urban areas. As a result of emerging new forms of poverty, there is a dire need to re-examine and re-visit urban poverty in Malaysia. This study affirmed that social entrepreneurship organisations in Malaysia have tried to overcome the urban poverty through social entrepreneurship. The new framework has been developed as a result of this study. It shows that social entrepreneurship contributed to the organisational effectiveness. This result indicates that social entrepreneurship is important to increase the socio economy and achieve the organisation's mission. Therefore, this study has proven that social entrepreneurship is beneficial to Malaysians.